Pharmacokinetics of metronidazole in pregnant patients with bacterial vaginosis - Wang, Xin (2010)
OBJECTIVE: The present study was undertaken to investigate the pharmacokinetics of metronidazole in pregnant patients with bacterial vaginosis. METHODS: Twenty patients received metronidazole (Flagyl,(®) Pfizer, 235 East 42nd Street, NY, NY 10017) oral dose 500 mg twice a day for 3 consecutive days. Pharmacokinetic analyses of metronidazole were performed after a single oral dose on the morning of the day 4. RESULTS: Although absolute estimates of metronidazole total body exposure were highest in women during early term pregnancy, weight-corrected estimates of exposure maximum plasma drug concentration (C(max), ) and the area under the plasma concentration-versus-time curve (AUC(0-12)), along with apparent oral clearance and distribution volume, were not significantly different between women at early, middle, and late stages of pregnancy and were in the range of reported values for nonpregnant patients receiving a similar dose. CONCLUSIONS: The pharmacokinetic profile of metronidazole did not change at the different time points assessed during pregnancy.